The Effect Of Counseling to Modification the Lifestyle On Prevention Of Obesity In Adolescents - Anto Anto; Sumardi Sudarman; Erni Yetti R; Saskiyanto Manggabarani (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2017)
Obesity is a serious problem for teenagers and a global pandemic as well as the biggest chronic health problem for both advanced and developing countries. The purpose of this study is to prove the effect of counseling on lifestyle modification on obesity prevention. Design of Quasy Experiment Study